Studi Kasus Peran Griya Musika Sukawati Cressendo Dalam Membangun Ekosistem Seni Musik Lokal Bali - Brill Obed Sabath; I Wayan Mudra; I Ketut Sariada (Institut Seni Indonesia Denpasar, 2025)
Purpose: This study aims to analyze the role of Griya Musika Sukawati Cressendo as a music education institution in building a local music arts ecosystem in Gianyar, Bali. Method: This research uses a qualitative research method with data collection through observation, interviews, and document studies. The results of the study show that Griya Musika Sukawati Cressendo has a significant role in the local music arts ecosystem in Gianyar. They not only provide quality music education, but are also active in developing the talents of local musicians, preserving traditional Balinese music, and creating a space of expression for musicians to work and collaborate. Result and Discussion: A SWOT analysis revealed that the institution's strengths lie in its comprehensive curriculum and qualified teaching staff. However, its weaknesses may lie in limited accessibility for underprivileged communities. Significant opportunities are seen in potential collaborations with the tourism industry and arts festivals in Bali, as well as the growing interest in music among the younger generation. Meanwhile, threats come from the globalization of music, which could shift preferences or the lack of clear career paths for graduates. Implication: The implications of this research emphasize that local music education institutions have great potential as a main pillar in the sustainability and revitalization of the arts and culture ecosystem, and provide strategic guidance for the development of similar models in other regions to balance cultural preservation with artistic innovation.